2016
DOI: 10.1039/c5dt04517g
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the synthesis of solvent-free Mg(B3H8)2

Abstract: This communication presents a novel and solvent-free method to synthesise Mg(B3H8)2 via the gas-solid reaction between B2H6 and Mg2NiH4, which overcomes the limitations of wet chemical methods requiring solvent removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…[39] Figure 1E shows the morphology of the purified product. [39] Figure 1E shows the morphology of the purified product.…”
Section: Regeneration Of Nabhmentioning
confidence: 99%
“…[39] Figure 1E shows the morphology of the purified product. [39] Figure 1E shows the morphology of the purified product.…”
Section: Regeneration Of Nabhmentioning
confidence: 99%
“…7 and 8) and BH 4 − (ref. 15 Ouyang et al 16 reported a method for in situ formation of cycle stable CeH 2.73 -MgH 2 -Ni nanocomposites, from the hydrogenation of as-melt Mg 80 Ce 18 Ni 2 alloys. However, when these materials were applied for commercial purposes, MgH 2 and LiBH 4 met with the problems of high dehydrogenation temperature and poor hydriding/ dehydriding kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The study on rehydrogenation from the intermediates was mainly focusing on Mg(B 3 H 8 ) 2 . 15,17,18 By controlling the decomposition in a relatively low temperature range from 200 to 285°C, Mg ( 19 Stable closo-borates such as MgB 12 H 12 and stable Mg-B-H polymers have also been widely discussed as the intermediates, which will hinder the reversible hydrogen sorption. 11,12,20 Apparently, the higher the borate formed in the desorption process, the more hydrogen might reversibly be stored.…”
Section: Introductionmentioning
confidence: 99%